Paveldas Lietuvos statybų vizijos kontekste - Bučas, Jurgis; Čepaitienė, Rasa; Gražulevičiūtė-Vileniškė, Indrė; Mlinkauskienė, Aušra (Journal of Architecture and Urbanism, 2007)
Heritage in the context of Lithuanian construction vision The part of heritage created during construction processes is analysed in the paper. In foreign countries the term “built heritage” is used to define the entire legacy of construction activities which is in the disposition of contemporary society. The term “built heritage” is not used in the Lithuanian heritage preservation law. In this paper the aspects concerning the meaning of the term “built heritage” are not discussed, attention is concentrated on the analysis of miscellaneous social and economic significance of this product of construction activities as a cultural good. Challenges concerning preservation of cultural goods provided by construction activities and development prospects of these activities are revealed. A chronological table of heritage preservation objectives and means in the context of the Lithuanian construction vision is also presented. Article in Lithuanian. Santrauka. Aptariama ta praeities palikimo dalis, kuri suku riama statybos procese. Užsienio šalyse statybinės veiklos palikimui, kuriuo disponuoja šiuolaikinė visuomenė, nusakyti vartojamas terminas statybinis paveldas. Lietuvos Respublikos paveldosaugos teisėje tokio termino nėra. Straipsnyje neliečiami šio termino reikšmės aspektai, bet nagrinėjama šio statybinės veiklos produkto, kaip kultūros gėrybės, daugialypė socialinė ir eko nominė reikšmė, iššūkiai, susiję su statybinės veiklos kultūros gėrybių apsauga ir šios veiklos plėtros perspektyvomis, pridedama lentelė, kurioje chronologine tvarka pateikiami paveldosaugos tikslai ir priemonės statybų vizijos kontekste. Reikšminiai žodžiai: statybinis paveldas, integrali statybinės veiklos gėrybių apsauga, rinkos kompensacija, Lietuvos statybų vizija. First published online: 21 May 2013